Development of Instagram-Based Teaching Materials For Personal Social Guidance Services For Students Of Krian State Junior High School I - Ruse Rahmawati Wulandari; Nyoman Sudana Degeng; Nurmida Catherine Sitompul (Jurnal Mantik, 2022)
The purpose of this development is to produce an Instagram-Based Teaching material to serve Student Social Personal Guidance. The selection of this model is based on the consideration that this model is easy to understand, systematically developed, and based on the theoretical foundation of the developed learning design. The development process involved (1) learning design experts (2) content experts in the field of study (3) media experts, (4) individual trials, (5) small group trials (6) field trials, and (7) trials. colleagues, to provide feedback and suggestions for improvement. The results of this development research are that this Instagram-based teaching material product has a material feasibility level of 97.33%, a learning design feasibility 94.28%, and a learning media feasibility 85.71%. While the small group trial rate is 90.69% and based on field trials 91.25% with very feasible qualifications and does not need to be revised. Based on the results of the study, it was concluded that using Instagram-based teaching materials could improve the Social Personal Guidance Service for Students of SMP Negeri I Krian. The implication of this research is that Instagram-based teaching materials can be used as a way to improve Student Social Personal Guidance Services.